2014
DOI: 10.1007/s00018-014-1667-3
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 and its variants promote angiogenesis via upregulation of VEGF and VEGFR2

Abstract: Severe plasma ADAMTS13 deficiency results in the clinical disorder thrombotic thrombocytopenic purpura. However, other potential pathophysiological roles of ADAMTS13 in endothelial cell biology remain unexplored. The goals of this study were to understand the angiogenic pathways ADAMTS13 activates and to identify the important structural components of ADAMTS13 that stimulate angiogenesis. Incubation of human umbilical vein endothelial cells (HUVEC) with 150 ng/mL (1 nM) of recombinant human ADAMTS13 induced VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…(22, 23) Placenta is an excellent model tissue to study angiogenesis and cell invasion. Incubation of HTR-8/SVNEO cells with 0-8 nM of recombinant full-length ADAMTS13 for 48 hours resulted in significantly increased proliferation of the trophoblastic cell line in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(22, 23) Placenta is an excellent model tissue to study angiogenesis and cell invasion. Incubation of HTR-8/SVNEO cells with 0-8 nM of recombinant full-length ADAMTS13 for 48 hours resulted in significantly increased proliferation of the trophoblastic cell line in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of excessive VEGF, ADAMTS13 promotes angiogenesis by upregulating VEGF and phosphorylation of VEGFR2. (22, 23) In the presence of excessive VEGF, ADAMTS13 appears to inhibit angiogenesis by competing with VEGF for binding to its receptor VEGFR. Our results are consistent with the proangiogenic effect of ADAMTS13 previously found in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that treatment of mice with rADAMTS13 induced a significant increase in VEGFR-2 phosphorylation ( Figure 4K), which is consistent with a recent in vitro study. 22 Immunohistochemical quantification indicated 44% and 64% increases in CD13…”
Section: A M T S 1 3 -/ -A D a M T S 1 3 -/ -mentioning
confidence: 99%
“…Indeed, ADAMTS13 was recently reported to increase VEGFR-2 phosphorylation and promote proliferation and migration of human umbilical vein endothelial cells in vitro. 22 However, whether ADAMTS13 plays a role in vascular regeneration in vivo remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the association could be explained by pathways responding to ADAMTS13. For example, there is preliminary evidence that ADAMTS13 upregulates vascular endothelial growth factor, a protein involved in angiogenesis that may contribute to the development of type 2 diabetes [35,36]. ADAMTS13 may similarly activate other pathways that lead to the development of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%